PENGALAMAN RELIGIUS DALAM MEDITASI TRANSENDENTAL - Erba Rozalina Yuliyanti (TOLERANSI: Media Ilmiah Komunikasi Umat Beragama, 2012)
This study tries to identify and analyse two types of thought, i.e. Western (Psychologists) and Islam thought (Sufist) in dealing with the phenomena of Religius experience. According to William James Religius experience is the experience of feeling close to something sacred. These experiences occur directly and emergent, but lead to the strenghthening of religioun and faith to the Creator. In the other hand, in Tasauf, the Religius experience is an esoteric experience or mystical experience. These experiences can be found through the Tarekat namely dzikir or muraqabah, in Psychology named Transendental Meditation. This method aims to strenghthen faith in the real aqidah and moral purity. In Psychology, the Religius experience which is gained in all religion teaching has many psychological dynamics: the object of the mind, stimulating, and positive perception of the sacred. Therefor, these dynamics will produce the spiritual health for those who do